Critical Appraisal of Emergency Medicine Education Research: The Best Publications of 2014. (16th October 2015) - Yarris, Lalena M.; Juve, Amy Miller; Coates, Wendy C.; Fisher, Jonathan; Heitz, Corey; Shayne, Philip; Farrell, Susan E.
Abstract: Objectives: The objective was to critically appraise and highlight rigorous education research study articles published in 2014 whose outcomes advance the science of emergency medicine (EM) education. Methods: A search of the English language literature in 2014 querying Education Resources Information Center (ERIC), PsychINFO, PubMed, and Scopus identified 243 EM‐related articles using either quantitative (hypothesis‐testing or observational investigations of educational interventions) or qualitative (exploring important phenomena in EM education) methods. Two reviewers independently screened all of the publications using previously established exclusion criteria. Six reviewers then independently scored the 25 selected publications using either a qualitative or a quantitative scoring system. Each scoring system consisted of nine criteria. Selected criteria were based on accepted educational review literature and chosen a priori. Both scoring systems use parallel scoring metrics and have been used previously within this annual review. Results: Twenty‐five medical education research papers (22 quantitative, three qualitative) met the criteria for inclusion and were reviewed. Five quantitative and two qualitative studies were ranked most highly by the reviewers as exemplary and are summarized in this article. Conclusions: This annual critical appraisal series highlights seven excellent EM education research studies, meeting a priori criteria and published in 2014. Methodologic strengths in the 2014 papers are noted, and current trends in medical education research in EM are discussed.